Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis - Muhammad Roqibun; Dewita Suryati Ningsih; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis in order to determine the influences of Work Motivation and Work Dicipline either simultaneously or partially on Employee Performance in Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis. The methodology in this study is: Work Motivation and Work Dicipline significant influence on employee performance in Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis and the dominant factor affecting the performance of employees is Work Dicipline. While the population in this study is the employees on Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis which amounted to 32 people, with a total sample of 32 respondents. Multiple Linear Regression Analysis method by using SPSS version 17. Simultaneous regression (F test) showed that the independent variables studied (Work Motivation and Work Dicipline) together (simultaneously) have a significant influence on the dependent variable (employee performance). The magnitude of the influence that (R2) by the two independent variables together against the dependent variable, while the remaining is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Work Motivation and Work Dicipline) has a significant influence on Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis the dependent variable (employee performance). Dominant variables affecting employee performance in Badan Pendidikan dan Pelatihan Pegawai Kabupaten Bengkalis is Work Dicipline where the value of t-counted highest compared with other independent variables.Keywords: Work Motivation, Work Dicipline and Employee Performance